2018
DOI: 10.1186/s12954-018-0213-2
|View full text |Cite
|
Sign up to set email alerts
|

High willingness to use rapid fentanyl test strips among young adults who use drugs

Abstract: BackgroundSynthetic opioid overdose mortality among young adults has risen more than 300% in the USA since 2013, primarily due to the contamination of heroin and other drugs with illicitly manufactured fentanyl. Rapid test strips, which can be used to detect the presence of fentanyl in drug samples (before use) or urine (after use), may help inform people about their exposure risk. The purpose of this study was to determine whether young adults who use drugs were willing to use rapid test strips as a harm redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
58
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(63 citation statements)
references
References 27 publications
(23 reference statements)
1
58
0
Order By: Relevance
“…Other interventions that may be effective aids in assessing overdose risk include point-of-use testing, also known as drug checking, and qualitative user discernment of street heroin. Recent research has shown a high willingness among younger, US-based injection drug users to utilize fentanyl test strips [ 83 ], but the hypersensitivity of on-the-market fentanyl test strips raises questions about their efficacy in helping injectors to quantify risk. Harm reduction interventions focusing on “universal precautions,” i.e., consistent use of drug sampling, may be more effective than point-of-use fentanyl testing.…”
Section: Discussionmentioning
confidence: 99%
“…Other interventions that may be effective aids in assessing overdose risk include point-of-use testing, also known as drug checking, and qualitative user discernment of street heroin. Recent research has shown a high willingness among younger, US-based injection drug users to utilize fentanyl test strips [ 83 ], but the hypersensitivity of on-the-market fentanyl test strips raises questions about their efficacy in helping injectors to quantify risk. Harm reduction interventions focusing on “universal precautions,” i.e., consistent use of drug sampling, may be more effective than point-of-use fentanyl testing.…”
Section: Discussionmentioning
confidence: 99%
“…This information empowers individuals who use drugs to make better-informed decisions about whether, where, how, or with whom to consume the tested substance, which is hoped to trigger behaviour change towards safer drug use practices and reduced overdose risk. In light of the opioid overdose public health emergency and emerging promising results with point-of-care fentanyl drug checking in different settings (Tupper et al 2018;Krieger et al 2018), fentanyl-specific drug checking was added by ANKORS as an optional test for festival attendees in 2017.…”
Section: Introductionmentioning
confidence: 99%
“…To date, no randomised clinical trials have examined the e cacy of rapid fentanyl test strips in combination with behaviour change intervention for the prevention of opioid overdose events. Our pilot study of young people at risk of fentanyl exposure demonstrated high willingness to use fentanyl test strips as a harm reduction tool, and the feasibility of a brief training module for non-expert use (14,16). Furthermore, positive test strip results were associated with drug risk behaviour changes (16).…”
Section: Discussionmentioning
confidence: 77%
“…Sample size/power calculations are based on ndings from our pilot intervention study (14). In this study, 37% of participants reported a lifetime history of overdose, and 10% reported a suspected fentanyl-related overdose in the past six months.…”
Section: Sample Sizementioning
confidence: 99%
See 1 more Smart Citation